Maternal Eating Behavior in Low-Income Mothers Influences Attitudes Toward Infant Feeding. (7th June 2021) - Kebbe, Maryam; Altazan, Abby; Beyl, Robbie; Gilmore, Anne; Redman, Leanne
Abstract: Objectives: Eating behavior is established early in life, influences infant development and health, and is likely to originate with the mother. We examined if maternal eating behaviors influenced attitudes towards infant feeding styles and whether these associations differed by infant feeding mode (breastfeeding and formula-feeding). Methods: This was an observational study in 35 low-income mother-infant dyads. Postpartum women (≥18 years old, 25 ≤ BMI < 40 kg/m 2 ) in the Louisiana Women, Infants, and Children (WIC) program completed the Eating Inventory and Infant Feeding Styles Questionnaire to assess maternal eating behavior (dietary restraint, disinhibition, and perceived hunger) and infant feeding styles (restrictive feeding, responsive feeding, and pressuring/overfeeding), respectively, 8 weeks after delivery. Linear models with fixed effects were computed with maternal age, BMI, and maternal eating behavior as covariates using SPSS (p < 0.05 to indicate significance). Results: Thirty-four % of the mothers were breastfeeding (n = 12) and 66.0% were formula-feeding (n = 23). Infant feeding styles were not predicted by maternal eating behaviors (all p > 0.05). In mothers who breastfed, maternal dietary restraint was positively associated with infant pressuring/overfeeding ( β = 0.91, p < 0.05) and was different from those in the formula fed group (Δ = 1.37, p = 0.02). In addition, maternal disinhibition was negatively associated with restrictive infant feeding ( β = −0.53, p < 0.05) and was different from those in the formula fed group (Δ = −0.95, p = 0.003). Comparatively, in mothers who formula-fed, restrictive infant feeding was predicted by maternal disinhibition ( β = 0.42, p < 0.01; Δ = −0.95, p = 0.003) and maternal perceived hunger ( β = 0.43, p < 0.01; Δ = 0.71, p = 0.007). Conclusions: Maternal eating behavior is associated with infant feeding styles only when feeding mode is considered. Interventions educating mothers on how their own eating behaviors have the potential to influence eating behaviors of their children are needed. Funding Sources: USDA Small Grants Program and the NIH (T32DK064584, and U54 GM104940).